2009
DOI: 10.1002/art.24503
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of STAT4, IL2/IL21, and CTLA4 polymorphisms in rheumatoid arthritis

Abstract: Objective. Recent advances have led to novel identification of genetic polymorphisms that are associated with susceptibility to rheumatoid arthritis (RA). Currently, 5 loci (HLA, PTPN22, TRAF1/C5, TNFAIP3, and STAT4) have been consistently reported, whereas others have been observed less systematically. The aim of the present study was to independently replicate 3 recently described RA susceptibility loci, STAT4, IL2/ IL21, and CTLA4, in a large Dutch case-control cohort, and to perform a meta-analysis of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
3
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 20 publications
5
61
3
2
Order By: Relevance
“…The SNP rs6822844 for IL-2/IL-21 was investigated for associations with the disease and for associations with autoantibody status in a Dutch RA cohort. IL-2/IL-21 rs6822844 showed a clear trend toward association with RA [65] . The KIAA1109-TENR-IL2-IL21 region has been associated with a wide variety of autoimmune diseases like type 1 diabetes (T1D) [66] , ulcerative colitis [67] , Crohn's disease [68] , celiac disease, Graves' disease (GD) [66] , systemic lupus erythematosus (SLE) [69] , psoriatic arthritis [70] , and juvenile idiopathic arthritis [71] .…”
Section: The Il-2 Familymentioning
confidence: 92%
“…The SNP rs6822844 for IL-2/IL-21 was investigated for associations with the disease and for associations with autoantibody status in a Dutch RA cohort. IL-2/IL-21 rs6822844 showed a clear trend toward association with RA [65] . The KIAA1109-TENR-IL2-IL21 region has been associated with a wide variety of autoimmune diseases like type 1 diabetes (T1D) [66] , ulcerative colitis [67] , Crohn's disease [68] , celiac disease, Graves' disease (GD) [66] , systemic lupus erythematosus (SLE) [69] , psoriatic arthritis [70] , and juvenile idiopathic arthritis [71] .…”
Section: The Il-2 Familymentioning
confidence: 92%
“…Care was taken to make sure that the patients matched the diagnostic criterias and didn't suffer from chronic diseases such as chronic viral infections (Elsaesser et al, 2009), SLE (Sarra et al, 2010), Rheumatoid Arthritis (Daha et al, 2009), Psoriasis (Liu et al, 2008) and Inflammatory bowel diseases (Liu et al, 2009). Written consent was obtained from all the patients concerned in order to perform this study.…”
Section: Methodsmentioning
confidence: 99%
“…While other polymorphisms within the CTLA4 gene appear to be associated with RA, [78][79][80] an GA SNP in the 3′ untranslated region (CT60; rs3087243) has received a more thorough investigation, especially in European populations. 37,52,[80][81][82] Although previous case-control studies in various populations have suggested a possible association of CTLA4 alleles with RA, the results of these studies are often inconclusive and are sometimes contradictory. A large cohort (n cases/controls = 2,370/1,757) from the North American Rheumatoid Arthritis Consortium (NARAC) and the Swedish Epidemiological Investigation of Rheumatoid Arthritis (EIRA) collections, provided support for an association of CTLA4 (CT60 allele) with the development of RA, but only in the NARAC cohort (OR = 1.1, 95% CI: 1.0-1.2; P = 0.004).…”
Section: Ctla4 Is Associated With Ra Pathogenesismentioning
confidence: 99%